Pengaruh Perbandingan Runner Terhadap Performa Turbin Vertikal Bertingkat Dua - Ade Sunardi; Yunan Hanun (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2016)
Wind energy is an alternative energy resources that abundant, enviromentally friendly and potential to be develop. The Utilization of wind energy can be applied at wind turbine. Ratio of vane amount as a runner was the variable that use on this research such as . Research use natural windfor 24 hours and data became fluctuatif. Data test obtain ratio runner 6:10 have greatest rotational speed, which is 373 rpm and mean rotational speed is 83.42 rpm. Runner ratio 6:12 have lowest rotational speed 291 rpm and mean rotational speed is 20.13